Malaria parasite burden and heterogeneity of risk factors among Central African Republic refugees: a cross-sectional study in the Gado-Badzere refugee camp in Eastern Cameroon - Nematchoua Weyou, Zidedine; Djemna Djieyep, Felicite; Ning Teh, Rene; Lontsi-Demano, Michel; Dieng, Cheikh Cambel; Bamou, Roland; Lo, Eugenia; Kuokuo Kimbi, Helen; Ule Ngole Sumbele, Irene (Frontiers in Tropical Diseases, 2024)
BackgroundRefugees are vulnerable populations especially in malaria endemic areas where the disease claims many lives and constitutes an emerging challenge for humanitarian response. This study assessed how the influx and settlement of Central African Republic (CAR) refugees influences malaria burden in the Gado-Badzere refugee camp, Eastern Cameroon.MethodsA cross-sectional malariometric survey was conducted between November 2022 and October 2023 in 324 households comprising 1,304 individuals aged 1 month and above. Malaria parasite burden was determined using rapid diagnostic tests (RDTs) and Giemsa-stained microscopy. Demographic characteristics, malaria risk factors, treatment-seeking behaviors and costs to cure malaria were assessed using semi-structured questionnaires.ResultsOf the 1,304 participants, 525 (40.3%) were malaria parasite positive with moderate geometric mean parasite density (GMPD) of 1100 parasites/μl of blood. Plasmodium falciparum was the main species (99.8%), with mixed P. vivax infections (0.2%). Insecticide treated net (ITN) ownership was 53.7%, but its utilization was significantly low (22.4%) (P < 0.001). Reason for no ITN ownership was net damaged (74.7%). Net insufficiency (77.8%) accounted for non-frequent ITN use. Mean expenditure to treat malaria in the hospital was higher (USD 13.64 ± 8.67) than auto-medication (USD 1.13 ± 1.18). Significantly, malaria parasite prevalence and risk were higher for 0-5 years age (43.7%, OR = 1; P = 0.02), residents of sector 8 (49.2%, OR = 2.53; P < 0.001) of the camp, non-frequent ITN users (41.7%, OR = 2.08; P < 0.001), people living around stagnant water (44.4%, OR = 1.55; P < 0.001) and during the rainy season (43.5%, OR = 1.31; P = 0.02). The GMPD/µl was significantly higher in the 0-5 years age group (1456, P < 0.0001), inhabitants of sector 9 (1626, P = 0.04) and participants living around stagnant water (2097, P = 0.01).ConclusionThe malaria burden in CAR refugees may represent the reservoir for malaria transmission, especially with the circulation of P. vivax. The improper use of ITNs could be ameliorated through sensitization. Seasonal chemoprevention mainly during the rainy season and Indoor Residual Spraying (IRS) might be implemented for effective malaria control in refugee settings.